Evaluation of revegetation techniques for roadside construction sites. Issue 3 (3rd July 2017) - Hilvers, George; Hopkinson, Leslie; Davis, Eric
Abstract: Vegetation is often used to control erosion on right-of-way construction sites, but disturbed conditions provide challenges. This research evaluated the impact of common techniques for preparing seedbeds. The study assessed the use of topsoil, and the use of a hydraulic erosion-control product was compared to straw. Experimental seed mixtures were evaluated to understand how native and non-native seeds performed. The intent was to identify critical practices to use in general seeding and mulching specifications. A plot study was conducted comparing vegetation established during one growing season. Treatments included combinations of seed mixture, topsoil treatment, and mulch types. Three seed mixtures were considered: (1) currently used mixture, (2) a warm-season experimental mixture, and (3) a cool-season experimental mixture. Plots with topsoil and no topsoil were compared, and both straw and hydraulic erosion control products were considered. Ground cover, compaction, and biomass were evaluated. Results suggest that alternative seed mixtures that include native and low-threat-level species can provide adequate cover to meet permitting requirements in the first growing season. The warm-season seed mixture provided less cover than the other two mixtures after eight days, but no differences were determined in ground cover among the three seed mixtures at the end of the growing season. Initial germination was improved with hydraulic mulch, but long-term cover was equivalent between hydraulic and straw mulch. Topsoil application would not be recommended if the soil contains undesirable species, and the use of organic amendment products may be more desirable than topsoil alone; however, specifications need to allow the use of these products.